PENGARUH UTILITARIAN VALUE, HEDONIC VALUE, BROWSING, FELT URGE TO BUY IMPULSIVELY TERHADAP IMPULSE BUYING - Asiska, Servina; Sari, Mareta Kemala; Ihsani, M Faridh; Hendayani, Dwi; Al Anshori, M Sabil; Muluk, Makrifadli (STIE Perbankan Indonesia, 2024)
This research examines the influence of utilitarian values, hedonic values, browsing, and feeling the urge to buy impulsively on consumers' impulsive buying behavior. The survey was conducted on 103 respondents and the data was analyzed using SEM. The results show that utilitarian and hedonic values ​​have a positive effect on browsing, which in turn influences impulse buying and ultimately impulsive buying. These findings contribute to marketing strategies to encourage impulse purchases and understanding the factors that influence them. Keywords: Utilitarian Value, Hedonic Value, Browsing, Impulse Buying, Impulse Buying.